Digital Religion and Hybrid Practices: Negotiating Ritual and Authority Within Jama’ah Tabligh in Indonesia - Ria Hayatunnur Taqwa; Ali Akhbar Abaib Mas Rabbani Lubis (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This article examines the transformation and digital adaptation of Jama‘ah Tabligh in the digital era, with a focus on the negotiation and reconfiguration of ritual communication in online spaces. The central issue addressed is the tension between the group’s traditional reliance on khuruj (missionary journeys) and face-to-face interactions, and the adoption of digital platforms that redefine authority and identity. This study employs a qualitative approach by analysing digital proselytizing content, observing practices on platforms such as YouTube, WhatsApp, and Instagram, conducting a critical review of relevant secondary literature, and carrying out in-depth interviews with selected members of Jama‘ah Tabligh. Indonesia is taken as the primary context of analysis while incorporating transnational dimensions to situate local practices within global networks. The findings indicate that digitalization has fostered more personal, visual, and participatory forms of religious expression, while simultaneously contributing to identity fragmentation and a redistribution of authority from seniority-based hierarchy to algorithmic visibility. Ritual communication, which was previously centered in markaz and physical khuruj, has expanded to include digital sermons, podcasts, and visual quotations, generating hybrid forms of piety that combine the values of Jama‘ah Tabligh with the logic of social media. This shift not only demonstrates resilience and adaptation but also raises epistemological challenges, including the risks of oversimplification, exclusion, and debates over authenticity. The article concludes that digitalization is not merely a means of disseminating proselytizing content but also reconstructs the structures of piety, authority, and collective identity in contemporary Islam in Indonesia. The implications extend to debates on digital religion and the sociology of transnational Islam, highlighting how non-political movements such as Jama‘ah Tabligh recalibrate their spiritual mission within the global network society.